Analisa Kapuasan Pelanggan Terhadap Kualitas Pelayanan PDAM Tirtanadi Cabang Padang Bulan - Purba, Fauzanolo; Haniza, Haniza; Siregar, Ninny (JOURNAL OF INDUSTRIAL AND MANUFACTURE ENGINEERING, 2018)
This study aims to determine the level of customer satisfaction to service quality of the Regional Water Company Branch Padang Bulan. The research method used in this research is quantitative descriptive with a population of Branch PDAM Tirtanadi Padang Bulan customers. The sample in this study of 100 respondents who were taken to area probability sampling technique. Data taken with the questionnaire and interview, while data analysis is descriptive percentages. The results showed that overall levels of customer satisfaction to service quality, including both the amount of 63.66%, which means that customers are satisfied with the service that has been provided by PDAM Tirtanadi Branch Padang Bulan. Elements of customer satisfaction to service quality which is in poor category there are 7 of Serviceability, service procedures, disciplinary care workers, care workers responsibility, fairness, service costs, and assurance of service schedules. While elements in both categories there are S of product quality, service requirements, clarity of service personnel, capability of the service, speed of service, justice get service, politeness and friendliness of staff cost certainty and convenience services environment.